Disentangling multiproxy temperature reconstructions from the subtropical North Atlantic - Repschläger, Janne; Weinelt, Mara; Schneider, Ralph; Blanz, Thomas; Leduc, Guillaume; Schiebel, Ralf; Haug, Gerald H. (Frontiers in Ecology and Evolution, 2023)
Reliable reconstruction of past sea surface temperature (SST) is of prime importance for understanding the Earth’s sensitivity to external forcing. Yet, it remains a major challenge in paleoceanography because comparison between SST estimates from different proxies reveal mismatches and raise the question as to what the contrasting proxies actually record. A better understanding of these mismatches in the light of seasonal occurrence of the proxy bearing organisms (archives) and water mass changes help to assess climate models. Here, we analyze data from the last deglaciation using a sediment core site situated at the northern boundary of the North Atlantic subtropical gyre influenced by fast latitudinal migrations of the subtropical Azores Front (AF) and resulting changes in water masses that may affect the SST records. Differences between the SST estimates from different deglacial SST reconstructions obtained from (1) Mg/Ca in planktic foraminifer tests, (2) alkenone UK’37, and (3) planktic foraminifer assemblages (SIMMAX), are assumed to result from the ecology of the proxy bearing organisms, and are assessed for the impact on different SST reconstructions from local seawater d18O (d18Ow) reconstructions. The general trends of SSTs from all four proxies confirm the well-known deglacial succession of warm and cold events. Mismatches between amplitudes of temperature changes are explained by differences in the phenology of the proxy-bearing organisms and local changes in hydrography. The combination of d18O and SST from the three different archives of d18Ow reconstructions may cause offsets that exceed the climate driven signals.